IMPLEMENTATION OF ARTICLE 127 OF LAW NO. 35 OF 2009 ON NARCOTIC ABUSE IN THE IMPLEMENTATION OF EARLY DETECTION OF URINE TESTS CASE STUDY OF NORTH SUMATERA PROVINCE BNN - Juita Novalia Br Barus; Sumarno; Yasmirah Mandasari Saragih (PT. Sinergi Legal Publisher, 2024)
This study examines the implementation of Article 127 of Law No. 35 of 2009 concerning Narcotics, especially in North Sumatra Province, with a focus on the use of urine tests as an early detection tool for drug abuse. Through doctrinal and qualitative research methods, this study integrates field data obtained from direct visits to the National Narcotics Agency of North Sumatra Province (BNNP Sumut). The results of the study indicate that urine tests have a significant role in early detection, but there are limitations in their effectiveness due to low sensitivity and specificity, as well as variability in results influenced by various factors. This study also explores the implementation of the rehabilitative approach regulated in the same article, finding that despite infrastructure and budget challenges, the rehabilitative approach is more effective in the long term compared to the criminal approach which often does not address addiction problems holistically. Recommendations from this study are the expansion of rehabilitation facilities, increasing budget allocation for rehabilitation, and developing a more comprehensive preventive approach involving education and public awareness about the dangers of drug abuse to reduce the prevalence of drug abuse in the community.